Potential Distribution of Cathodic Protection using Mg as a Sacrificial Anode - Elaibi*, Alaa Ibrahim (Nahrain University College of Engineering Journal, 2014)
Cathodic protection in the sacrificialsystem is essentially a controlledelectrochemical cell; corrosion on theprotected structure is shifted to theanode. When the anode material iscoupled to steel, they behave anodicallyand discharge current.In this work,magnesium used as sacrificial anode forthe protection of carbon steel rod thatburied in soil with resistance of 1000,1400, 1800, and 2200?/cm that simulatewide range of resistance of Iraqisoil.Potential distribution in differentpositions between sacrificial anode andthe protected structure was measuredwith respect to copper - copper sulfateelectrode, showing that the conditionsfor the sacrificial anode for theprotection of carbon steel rod andsimulate with contours.The result showthat the increasing of soil resistivity isreduces anode life and impairs itsperformance. In addition, the changingof sacrificial anode is important becauseit consumed therefore, it is important tooptimize the distance of sacrificial anodefrom protected structure according tosoil resistivity so thatavoiding the polarization that causeshigh consumption rate of anode.